Application of topsis model based on game theory to reservoir water quality evaluation - Yang, Xu; Zhuang, Qing; Nie, Tangzhe (Italian journal of engineering geology and environment, 2024)
In view of the shortcomings of the single weighting method, the game theory method was adopted to optimize the combination of the subjective weight determined by the analytic hierarchy process (AHP) method and the objective weight determined by the entropy weight method. The technique for order preference by similarity to an ideal solution (TOPSIS) evaluation model based on the combination weighting of the AHP-entropy weight method-game theory was constructed for evaluating the water quality of Mopanshan Reservoir. The result obtained by the TOPSIS evaluation model was compared with the evaluation result of the grey relational model. The evaluation results showed that the water quality of Mopanshan Reservoir during the sampling period was Class I and II. The main factors affecting water quality were NH3-N (ammonia nitrogen) and pH value. The game theory-based combination weighting TOPSIS model proposed in this paper fully considers the effective information among various indicators, reduces the subjective arbitrariness of weighting, makes indicator weighting more scientific, and obtains more reasonable water quality evaluation results. It is worthy of application in similar water quality evaluation problems.